2019
DOI: 10.1016/j.nbd.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The UPR-PERK pathway is not a promising therapeutic target for mutant SOD1-induced ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, characterized by motor neuron death in the brain and spinal cord. Mutations in the Cu/Zn superoxide dismutase (SOD1) gene account for ~20% of all familial ALS forms, corresponding to 1%-2% of all ALS cases. One of the suggested mechanisms by which mutant SOD1 (mtSOD1) exerts its toxic effects involves intracellular accumulation of abnormal mtSOD1 aggregates, which trigger endoplasmic reticulum (ER) stress and activate its adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 67 publications
5
23
0
Order By: Relevance
“…Inhibition of eIF2α phosphatase reduced the phenotypes in TDP-43 mutant animal models (Vaccaro et al, 2013 ). However, neither genetic inhibition of the UPR via ablation of PERK, nor genetic UPR enhancement via ablation of GADD34, had a beneficial effect in mutant SOD1 mice (Dzhashiashvili et al, 2019 ). More recent studies in SOD1-iPSC and mouse models demonstrated that MNs are more sensitive to ER stress and identified a number of modifiers, including TUDCA, a bile acid derivative which is currently undergoing clinical trials in ALS (Thams et al, 2019 ; Paganoni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of eIF2α phosphatase reduced the phenotypes in TDP-43 mutant animal models (Vaccaro et al, 2013 ). However, neither genetic inhibition of the UPR via ablation of PERK, nor genetic UPR enhancement via ablation of GADD34, had a beneficial effect in mutant SOD1 mice (Dzhashiashvili et al, 2019 ). More recent studies in SOD1-iPSC and mouse models demonstrated that MNs are more sensitive to ER stress and identified a number of modifiers, including TUDCA, a bile acid derivative which is currently undergoing clinical trials in ALS (Thams et al, 2019 ; Paganoni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter mechanism, a problem of topology arises, similar to that mentioned above with α-synuclein, as it is unclear how cytosolic SOD1 is translocated into the ER lumen. It was reported that PERK haploinsufficiency has a deleterious effect on mSOD1 model mice [95], but these results were challenged in a recent study, which showed no significant effects in disease progression [96].…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 98%
“…Initial studies indicated that Perk haploinsufficiency accelerates experimental ALS in Sod1 transgenic mice, these mice had a reduced capacity to turn down synthesis of misfolded SOD1, leading to an early overload of the UPR [ 123 ]. Furthermore, the genetic ablation of GADD34 [ 124 ] and the inhibition of eIF2α phosphatase [ 125 ] delayed the disease onset and prolonged motor neuron survival. However, more recent studies performed on SOD1 mice showed that neither PERK haploinsufficiency, nor genetic UPR enhancement via ablation of GADD34, is beneficial for mutant SOD1 -induced motor neuron disease [ 126 ].…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 99%